2022
DOI: 10.3389/fenvs.2022.903074
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Taxon Congruence of Taxonomic and Functional Beta-Diversity Facets Across Spatial and Temporal Scales

Abstract: An intensively debated issue in ecology is whether the variations in the biodiversity patterns of different biological groups are congruent in space and time. In addition, ecologists have recognized the necessity of accounting for both taxonomic and functional facets when analysing spatial and temporal congruence patterns. This study aimed to determine how the cross-taxon congruence of taxonomic and functional beta diversity varies across space and time, using data from four floodplains at a continental scale.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…For example, Colina et al [82] found group-specific feeding preferences of zooplankton linked to phytoplankton traits. Lansac-Tôha et al [83] found low levels of cross-taxon (from algae to zooplankton and fish) congruence of taxonomic and functional beta diversity. Even though not directly related to studies across trophic levels, small bacterivorous and detritophagous rotifers increase with trophic state [84] indicating a link between algae and rotifers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Colina et al [82] found group-specific feeding preferences of zooplankton linked to phytoplankton traits. Lansac-Tôha et al [83] found low levels of cross-taxon (from algae to zooplankton and fish) congruence of taxonomic and functional beta diversity. Even though not directly related to studies across trophic levels, small bacterivorous and detritophagous rotifers increase with trophic state [84] indicating a link between algae and rotifers.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/w15081459/s1, Table S1: List of the 66 inspected studies with their publication year, studied habitat, country of provenance, journal name, impact factor, quartile rank, provision of traits, and application of the guild ratio [20][21][22]24,34,37,38,44,[47][48][49][50][51][52][54][55][56][57]80,83,; Table S2: Trait assignment for the 138 genera of phylum Rotifera [31,32,59,60,64,77,; Table S3: Rotifer genera with their traits and their cluster number as assigned by hierarchical, divisive clustering.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…We tested the hypothesis that rainfall rate is a significant driver of Amazon coastal species and that the considerable input of freshwater during the rainy season reduces the number of species, abundance, and diversity (Shannon index) of Amazon's beaches, as demonstrated for other sandy beaches in South America, e.g., [23,24]. In addition, since floods and strong hydro dynamism tend to homogenize the environmental characteristics and reduce the spatial variability of biological assemblages (i.e., beta diversity) [25][26][27], we expected lower habitat heterogeneity and beta diversity of macrobenthic assemblages during the rainy season-an expectation further reinforced by the possible lower number of species and individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Biodiversity surrogates require a trade-off between the surrogates' ability to re ect the distribution of unsampled species and the cost of sampling species in the eld (Gardner et al 2008;Lansac-Tôha et al 2022). This approach has been applied to numerous taxonomic groups in terrestrial (Corcos et al 2021;Verdinelli et al 2022) and aquatic ecosystems (Pakulnicka et al 2015;Spigoloni et al 2022).…”
Section: Introductionmentioning
confidence: 99%